Induction of systemic inflammation by hyaluronan and hsp70 in women with pre-eclampsia - Romão-Veiga, Mariana [UNESP]; Matias, Mariana Leticia [UNESP]; Ribeiro, Vanessa Rocha [UNESP]; Nunes, Priscila Rezeck [UNESP]; M. Borges, Vera Therezinha [UNESP]; Peraçoli, José Carlos [UNESP]; Peraçoli, Maria Terezinha S. [UNESP] (Elsevier, 2018)
Pre-eclampsia (PE) is a human pregnancy syndrome with abnormal activation of the innate immune response. The study evaluated the involvement of molecular structures called damage-associated molecular patterns (DAMPs), such as hyaluronan (HA) and heat shock proteins (Hsp) on NLRP1 and NLRP3 inflammasomes activation in peripheral blood monocytes. Twenty pre-eclamptic women, 20 normotensive pregnant women (NT) and 20 non-pregnant women (NP) were studied. Enzyme immunoassay was employed for the determination of HA, Hsp70 and High mobility group Box 1 (HMGB1) in plasma, as well as for the detection of Interleukin-1β (IL-1β), IL-18 and tumor necrosis factor alpha (TNF-α) in the supernatant of monocytes cultured with or without HA and Hsp70. The inflammasomes induction was evaluated by the quantification of mRNA for NLRP1, NLRP3, caspase-1, IL-1β IL-18, HMGB1 and TNF-α by qPCR in monocyte culture. The results showed significantly higher plasma levels of HA, Hsp70 and HMGB1 in pre-eclamptic women than in NT and NP women. Monocytes from women with PE showed endogenous activation of NLRP1 and NLRP3 inflammasomes, and expressed high amounts of IL-1β IL-18, HMGB1 and TNF-α. The stimulation of monocytes with HA increased the gene expression of NLRP1, NLRP3, caspase-1, TNF-α IL-1β HMGB1 and IL-18 and the production of IL-1β in pre-eclamptic women. Monocytes cultured with Hsp70 produced elevated levels of IL-1β and TNF-α through a mechanism independent of inflammasomes activation. These results suggest the participation of these DAMPs in the systemic inflammatory response that is characteristic of PE.
Keywords: Cytokines; DAMPs; Inflammasomes; Monocytes; Pre-eclampsia